Pengaruh Kompetensi, Disiplin, Dan Kompensasi Terhadap Kinerja Karyawan Pada Rumah Sakit Ibu Dan Anak Pembinaan Kesejahteraan Umat Muhammadiyah Kotagede - Aska Khuluki; Ignatius Soni Kurniawan (Universitas PGRI Yogyakarta, 2023)
This study aims to analyze the effect of competence, discipline, and pain on employee performance at Rumah Sakit Ibu dan Anak Pembinaan Kesejahteraan Umat Muhammadiyah Kotagede. This research is a quantitative study involving 60 employees of Rumah Sakit Ibu dan Anak Pembinaan Kesejahteraan Umat Muhammadiyah Kotagede. Data was taken using a questionnaire using a saturated technique. Data is processed using validity and reliability tests, classical assumption tests, and multiple linear regression analysis. The results of the study show that competency, discipline, and alarm have a significant effect on employee performance. The research implication states that initial improvements will lead to improvements in employee performance.